Efecto de inductores de resistencia sobre Rhizoctonia solani en el cultivo de arroz en la zona de Babahoyo – Ecuador - Vecilla Nicola, Luis Pedro (2025)
The present study aimed to evaluate the effect of resistance inducers on R. solani, the causal agent of sheath blight, in rice crops in the Babahoyo area, Ecuador. Two commercial varieties (IMPACTO and SFL-11) and six treatments were used, including salicylic acid (SA) at two doses (2.0 and 3.0 L/ha), fosetyl-aluminum (0.75 and 1.00 kg/ha), a chemical fungicide (propiconazole + tebuconazole), and a control without application. The experimental design was randomized complete blocks with an A × B factorial arrangement and three replications. The results showed that salicylic acid at 3.0 L/ha was the most effective treatment, achieving a significant reduction in the incidence (5.67%) and severity (5.67%) of the disease, with a control efficacy of 81.48%. In addition, this treatment significantly improved agronomic parameters such as plant height, number of tillers and panicles, 1000-grain weight and yield (8023.33 kg/ha in the IMPACTO variety). Fosetyl aluminum also reduced disease incidence and severity, although with less efficacy (up to 64.01%). The control variety without application recorded the highest incidence (31.33%) and severity (30.5%) values, as well as the lowest yield (6558.33 kg/ha). No significant differences were detected between varieties regarding disease incidence and severity, but there were differences in productive traits, where IMPACTO outperformed SFL-11 in yield. The economic analysis revealed that the highest net benefit was achieved with AS treatment at 3.0 L/ha in the IMPACTO variety, generating $3633.53/ha. This study concludes that the use of inducers such as salicylic acid constitutes a viable, effective, and sustainable alternative for the integrated management of R. solani in rice, reducing dependence on chemical fungicides and promoting sustainable and profitable cultivation.